May call waiting ka ba? [videorecording]: mga kuwento ng bakasyon - Cantada, Candy (Quezon City : Jesuit Communication, 2001)
In this half-hour documentary, Fr. Jett Villarin, SJ, Sr. Marjo Matias, ra, Bro. Armin Luistro, FSC, and Fr. Elmer Alforque, DCI talk about how they discerned and discovered their vocations. They also share their fears, their joys, and their lives as servants of God, like all of us who are called to saintlier lives - like all of us as well.
Keywords: Vacation (in religious orders, congregations etc.); Servants of God; Holy orders